A radical bioecological paradigm for design technologies with a transdisciplinary approach - Nava, Consuelo; Melis, Alessandro (TECHNE - Journal of Technology for Architecture and Environment, 2021)
This essay attempts to critically examine the proposed topic of “promotion of the architectural project as an interdisciplinary synthesis tool”, entrusting its possible cognitive trajectories to design experiments, based on transdisciplinary frontier research. Hoping to overcome a literature already referred to on the themes of the design of architecture and cities, a more radical discussion opens up concerning its “organic” forms and “ecological” structures. This debate draws on the themes of evolutionary biology in a key of eco-technological innovation, as a contribution to transformative resilience and circularity of resources, defining “a creative project” for architectures and the city, which are enabled to know the future.